The Impact of Land Conversion on Income and Food Security Status For Farmer Households in 5 Villages in Temon Sub-District, Kulon Progo District, 2017 - Anisa Nurpita; Latri Wihastuti; Ike Yuli Andjani (Magister Ilmu Administrasi Publik, 2017)
Preparation for the construction and development of NYIA airport in Temon sub district, Kulon Progo district, D.I. Yogyakarta province has caused displacement of people for their land, including farmers. Farmers affected are located in five villages that include Jankaran, Palihan, Sindutan, Glagah and Kebon Rejo. The objective of this resrarch is to analyze the impact of land conversion on farmer household incomes and food security status. The research used both primary and secondary data. Primary data was collected using structured questionnaire. Analysis of data was based on descriptive statistics and test of differences between paired samples. Results showed that land conversion has had a negative and significant influence on incomes of affected farmer households. The decline in household income of farmers in 5 villages in Temon sub district among other factors, is attributable to the reduction in farming land. Secondly, consequently, loss of farmer household income aggravated the vulnerability of the affected households to food insecurity. The number of farmer households that experienced food insecurity increased from 87 percent of all farmer households prior to land conversion to 90 percent after land conversion. Conclusions formed the basis for several policy recommendations to mitigate and if possible overcome the problem.